Modelling the demand for long-distance day trips to the Lake District - 406896 Greening, P. A. K.; Miles, J. C.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Berkshire : Tr ansport adn Road Research Laboratory, 1979)
08